2016
DOI: 10.1002/mus.25196
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the distal branches of the superficial fibular sensory nerve

Abstract: These results suggest that anatomical variations in the IDCN territory are very frequent in Japanese subjects. Muscle Nerve 55: 74-76, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This might be due to various anomalous innervations of the DSN to the IDCN territory. Our previous study (Hemmi et al, 2017) showed that "standard innervation type" (the IDCN territory being innervated by the IDCN alone) was in only 6.5% of cases and "sural only type" (the IDCN territory being taken by the DSN alone) was in 14.5% of cases. When the two groups were compared (standard innervation type vs. sural only type), a higher SNAP amplitude could be obtained in the "sural only type" by our method with SSEs (P=0.03) but not by the conventional method with a standard bipolar stimulator (P=0.76).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This might be due to various anomalous innervations of the DSN to the IDCN territory. Our previous study (Hemmi et al, 2017) showed that "standard innervation type" (the IDCN territory being innervated by the IDCN alone) was in only 6.5% of cases and "sural only type" (the IDCN territory being taken by the DSN alone) was in 14.5% of cases. When the two groups were compared (standard innervation type vs. sural only type), a higher SNAP amplitude could be obtained in the "sural only type" by our method with SSEs (P=0.03) but not by the conventional method with a standard bipolar stimulator (P=0.76).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study showed that variant innervations were more frequent in the IDCN than in the MDCN due to the anatomical relationship of the IDCN with the DSN (Hemmi et al, 2017). In 93.5% of the feet, the IDCN was partially or totally absent and its place was taken by the DSN.…”
Section: Introductionmentioning
confidence: 96%
“…Knowing the anatomical variants of this nerve ensures, in addition to better nerve utilization, a greater chance of preventing injuries to the distal branches involved in its harvesting procedure [24]. Simple electroneuromyography tests may be used for the non-invasive ascertainment of possible variations in the SFN terminal branching [11]. The preoperative application of these tests can be of great value to avoid iatrogenic injury to this nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In one participant, the SNAP was obtained on stimulating the superficial peroneal nerve but not the sural nerve. [ 18 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%